Marine-Derived Metabolites of S-Adenosylmethionine as Templates for New Anti-Infectives - Janice R. Sufrin; Steven Finckbeiner; Colin M. Oliver (Marine Drugs, 2009)
S-Adenosylmethionine (AdoMet) is a key biochemical co-factor whose proximate metabolites include methylated macromolecules (e.g., nucleic acids, proteins, phospholipids), methylated small molecules (e.g., sterols, biogenic amines), polyamines (e.g., spermidine, spermine), ethylene, and N-acyl-homoserine lactones. Marine organisms produce numerous AdoMet metabolites whose novel structures can be regarded as lead compounds for anti-infective drug design.